Penerapan Model Discovery Learning untuk Meningkatkan Kemampuan Bernalar Kritis dalam Pembelajaran PAKBP - Yongki Saputra; Sugiyana Sugiyana; Hartutik Hartutik; Galuh Arti Setyani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Catholic Religious Education and Ethics have an important role in shaping the character and spiritual attitude of students. However, in the learning process, Catholic Religious Education and Ethics often face challenges, especially caused by the influence of the digital era and instant mindset. This challenge becomes increasingly complex because teachers have not applied methods that are oriented to students in the learning process, resulting in an impact on the low critical reasoning skills that can be seen from students' learning outcomes. This study aims to analyze the effectiveness of the application of the Discovery Learning (DL) model in improving students' critical reasoning skills and the average completeness of learning outcomes of Catholic Religious Education and Ethics in Phase E. This class action research was carried out in four stages, namely planning, implementation, evaluation, and reflection, with class X respondents as many as 13 students. Data were obtained by observing changes in the behavior of the critical reasoning dimension and learning achievement tests at the end of each cycle. Data processing with descriptive and percentage analysis, in two cycles with the Discovery Learning (DL) model. Focusing on the critical reasoning dimension of the Pancasila student profile is intended to improve the cognitive and affective aspects in the learning process. The results showed that there was an increase in the cognitive aspects of students in the advanced category by 31%, from 23% in the first cycle to 54% in the second cycle. In the affective aspect, in terms of critical reasoning skills, there was an increase of 8% in the advanced category, from 23% in cycle 1 to 31% in cycle 2. The results of this classroom action research show that learning with the Discovery Learning model by focusing on one dimension of the Pancasila student profile can improve critical reasoning skills and student learning outcomes.